Original paper Modulation of the tissue defense system by squalene in cyclophosphamide induced toxicity in rats - Senthilkumar, Subramanian; Ebenezar, Kesavarao Kumar; Sathish, Venkatachalem; Yogeeta, Surinderkumar; Devaki, Thiruvengadam (Archives of Medical Science, 2006)
Introduction: Antineoplastic drug, Cyclophosphamide (CP), is a widely used drug that causes toxicity through its metabolites, phosphoramide mustard and acrolein. Squalene (SQ), an intermediate in the cholesterol metabolism has antioxidant and membrane stabilizing property. In the present study, the protective role of SQ towards the tissue defense system of the liver and kidney in the toxicity induced by CP was assessed. Material and methods: Normal Wistar albino rats were administered CP in a dose of 150 mg/kg b.wt., i.p., twice, for 2 consecutive days to induce toxicity. SQ, in a dose of 0.4 ml/day/rat p.o. was used to treat the toxicity induced by CP. Results: Significantly decreased activities of enzymic antioxidants [superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione-s-transferase (GST) and glutathione reductase (GR)], decreased levels of reduced glutathione and increased levels of thiobarbutric acid reactive substance (TBARS) were observed. These pathological alterations were significantly normalized during the treatment of SQ. Conclusions: CP toxicity increased the free radical levels in the tissues and affected the activities of the enzymic antioxidants. Increased levels of TBARS [a measure of lipid peroxidation (LPO)] and decreased levels of GSH (due to utilization for detoxification process) evidenced the damage to these tissues. Protection exerted by SQ could be due to free radical quenching, providing additional alkylation site to CP metabolites and by inducing enzymic antioxidant production in these tissues. In conclusions improved antioxidant defense system in the liver and kidney of the experimental rats confirms the protective role of SQ against CP induced toxicities.